Self-efficacy and academic performance in economics in the junior college - Marhaini Mohamed Amil. (2008)
The aim of this study was to investigate the relationship between self-efficacy and academic performance in Economics among junior college students. Self-efficacy is the belief in one's capabilities in performing a specific task. According to the theory of self-efficacy, the relationship between self-efficacy and self-regulated learning is a positive one, but the relationship between self-efficacy and anxiety is a negative one. Highly self-regulated learners generally have high self-efficacy which causes them to have low test anxiety, and hence are usually high academic performers.